PENGEMBANGAN MEDIA PEMBELAJARAN MONOPOLI PADA KONSEP FOTOSINTESIS KELAS XII IPA SMA - Pramartasari, Nora (BIOLOVA, 2025)
The purpose of developing to produce a product in the form of monopoly learning development media to strengthen the concept of photosynthesis material so that it is suitable and can be used as a learning medium by educators (teachers) and students. Development method usingresearch and development (RnD) and the development model used is the 4D model, this model consists of 4 development stages, namelydefine, design, develop, and disseminate. The results of the development of photosynthesis monopoly media products are related to students' interest in use Monopoly media as a learning medium in class received several very good responses with various percentages obtained, for enjoyment of the media it got 73%, Photosynthetic monopoly media was interesting to use 38%, increased learning motivation 30%, active learning 50%, motivated to find answers 36%, and a feeling of wanting to be directly involved in playing 27%. The feasibility of developing media from Biology Teachers received criteria for being suitable for use without revision with an average percentage of 92.31%. The conclusion of the development using photosynthesis monopoly media can be an alternative source of creative and innovative learning media, so that among students there is a sense of interest in learning, training cognitive and psychomotor skills simultaneously, as well as being a way of learning innovation for students to create learning. which is meaningful.